THE USE OF CORE MODEL OF LEARNING IN IMPROVING STUDENTS’ READING COMPREHENSION ABILITY - Cahyaningsih Cahyaningsih; Dede Rosyadi ZA (Program Studi Pendidikan Bahasa Inggris, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Muhammadiyah Cirebon, 2018)
The objectives of the research are to know how to implement of CORE model of learning in teaching reading comprehension ability and to find out the improvement of students in reading comprehension by using CORE model of learning. The subject of the study was the second grade students of SMPN 1 Jatibarang, Indramayu which consists of 31 students. The data of this research was collected by giving the pre-test and post-test. The data analyzed using statistical formula percentage technique. The result of the data analysis could be seen from the result of the post-test both in cycle 1 and cycle 2. The mean of the pre-test was 64.27, whereas the mean of post-test of cycle 1 was 75.21 while the mean of the post test of cycle 2 was 79.06. It indicated that the post-test score in cycle 2 is higher than in cycle 1. So, it could be concluded that the students who were taught by using CORE model of learning have a better achievements than before. Key Words: Reading Comprehension, Teaching Reading, Core model of learning